2020
DOI: 10.35429/jlde.2020.7.4.27.39
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to identify psychosocial risk factors at work: a systematic review

Abstract: The human factor within organizations is exposed to different types of risks, especially those that cause damage to their physical and psychological health, which if not identified and treated in time can generate irreversible damage to them. In recent years, investigations have been carried out that address the subject, in which different instruments have been implemented to identify and evaluate this phenomenon, so the purpose of this systematic review article was to analyze the instruments that allow identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The Copenhagen Psychosocial Questionnaire (COPSOQ) is an example of the most widely used instruments to assess PSR and has been used in various occupational sectors [ 20 ]. A systematic review and meta-analysis conducted by Molen et al [ 19 ] concluded by moderate-quality evidence that effort-reward imbalance, low procedural and relational justice, high work demand, low support from colleagues and supervisors, high emotional demand, and low decision authority would increase the incidence of stress-related disorders (20% to 90%). In a systematic literature review, Mccormack et al [ 16 ] also found that workload and work settings are the most common work demands and factors that contribute to burnout among applied psychologists.…”
Section: Introductionmentioning
confidence: 99%
“…The Copenhagen Psychosocial Questionnaire (COPSOQ) is an example of the most widely used instruments to assess PSR and has been used in various occupational sectors [ 20 ]. A systematic review and meta-analysis conducted by Molen et al [ 19 ] concluded by moderate-quality evidence that effort-reward imbalance, low procedural and relational justice, high work demand, low support from colleagues and supervisors, high emotional demand, and low decision authority would increase the incidence of stress-related disorders (20% to 90%). In a systematic literature review, Mccormack et al [ 16 ] also found that workload and work settings are the most common work demands and factors that contribute to burnout among applied psychologists.…”
Section: Introductionmentioning
confidence: 99%